Clusters in context: Towards a typology of industrial decarbonisation initiatives - Imogen Rattle; Peter G. Taylor (Geo: Geography and Environment, 2025)
Abstract Policy‐makers and researchers are increasingly focused on the decarbonisation of clusters of energy‐intensive industries. However, relatively little is known about the trajectory of different cluster decarbonisation initiatives. This paper aims to bring clarity to an emerging field. It highlights the evolving landscape of industrial decarbonisation initiatives, and the growing importance of clear definitions for effective communication and knowledge exchange among stakeholders. Drawing on insights from cluster theory, it proposes a typology of industrial cluster decarbonisation initiatives to understand and categorise different types of project. These four categories— ‘forerunner clusters’, ‘dispersed clusters’, ‘classic clusters’ and ‘dispersed sites’—allow a more focused understanding of the policy implications and challenges associated with each type. To demonstrate the application of the typology, the paper presents profiles of three cluster initiatives that illustrate some of the dynamics involved. Through this work, we seek to provide guidance for future research and policy development in the transition towards a low‐carbon industrial future.